Community perceptions and adaptation to climate change in coastal Bangladesh - Rahman, Mokhlesur M. (Curtin University, 2014)
This research examines local understandings and perceptions of climate change in two coastal villages in Southwest Bangladesh. Based on a combination of survey data and ethnographic field research, it shows how the livelihoods of the inhabitants of the two villages have been affected by various development interventions in the past, more recent changes in local weather patterns and their adaptation to these changes.These adaptive responses are shown to fall within a resilience framework.